PERSEPSI GURU TENTANG KOMPETENSI DIGITAL DAN KEMAMPUAN MEMBUAT MEDIA PEMBELAJARAN - Ahmad Mahyudin (STKIP PGRI Situbondo, 2022)
This study aims to determine the teacher's perception of digital competence in the ability of teachers and the practice of making learning media in schools. A quantitative research approach was used and a survey method was carried out, to collect data using a google form with 13 questionnaire items that returned the form the number of respondents was 64 school/madrasah teachers. Quantitative data analysis with SPSS version 24, including statistical descriptive analysis, mean value and standard deviation with one way sample test analysis. The results of the study found that the teacher's perception of digital competence and the ability to create media was the result of answers with an average of 4.34-3.94, that teachers had a good or even very good perception of digital competence for the digital knowledge section and digital users, excluding in digital security and programming capabilities. For the results of the analysis of the ability to make teacher learning media in schools/madrasah the average teacher is good and the teacher is able to make this, this is from the factors that encourage the rise of online learning and PJJ that have been experienced by teachers.